If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2r + -12 = -40 + 6r Reorder the terms: -12 + 2r = -40 + 6r Solving -12 + 2r = -40 + 6r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-6r' to each side of the equation. -12 + 2r + -6r = -40 + 6r + -6r Combine like terms: 2r + -6r = -4r -12 + -4r = -40 + 6r + -6r Combine like terms: 6r + -6r = 0 -12 + -4r = -40 + 0 -12 + -4r = -40 Add '12' to each side of the equation. -12 + 12 + -4r = -40 + 12 Combine like terms: -12 + 12 = 0 0 + -4r = -40 + 12 -4r = -40 + 12 Combine like terms: -40 + 12 = -28 -4r = -28 Divide each side by '-4'. r = 7 Simplifying r = 7
| 3y^2=-13y-4 | | 8y-28=0+y | | (3x+5x)+9= | | 3x+5x=23.3 | | (3n^2)-2n-5=0 | | 24=-2(22-b)+3(b-4) | | 4w^2-3=21 | | -2x-4=-4+5x | | -11+10z+100=4-10z+110 | | (2x+4)=59 | | 6-4*lnx=7 | | m^4+7m^2+12=0 | | 4(15x+25)=760 | | sinB=0.4848 | | 5x-12+7x+10+5x-12+7x+10= | | (.01x^2)+.6x+6.3=0 | | 9m-4(m+1)=(3m-20) | | 2(5)-2x=6 | | 6w+2=-4-w+1 | | 11x-2y=22 | | 3(x+2)=6(x-2)-3 | | 4x-2(x-4)=-5+4x+9 | | -12y+144=-9+-63y | | 3(x+2)=6(x-2) | | (.013x^2)-1.19x+28.24=9 | | 13=3(a)-14 | | ax+b=-e | | 18x=28x+120 | | 9(5-9a)=6(-3-3a) | | -5(8v-5)=345 | | 36-2(2x+1)=13x-2(13+x) | | x^2-4x=55 |